Wednesday

July 29, 2015

July 29, 2015

Posted by **Anonymous** on Wednesday, August 4, 2010 at 11:39am.

g+g+g=d

j+e=j

g^2=d

b+g=d

f-b=c

i/h=a(h>a)

a*c=a

- Math -
**jai**, Saturday, August 14, 2010 at 7:49amnote: remember that if we have two unknowns in an equation, we need also two equations (with the two unknowns) to solve for their values,,

first, work with the first and third given: (since both contains the same unknowns)

3g=d *substitute d to the other

g^2=d=3g *transpose all terms to one side and factor out g

g(g-3)=0 ; g=0 and g=3 [since there are two possible values for g, d should also have two possible values]

substituting to either equations you'll get:

at g=0, d=0 and at g=3, d=9

also, look at the seventh equation,, since a*c=a, c must be equal to 1,,

another is second equation,, since j+e=j, e must be equal to 0

next, find equations where you can substitute known values,, take the fourth equation,,

b+g=d *substitute respective values of g and d

at g=0, d=0, b=0 and g=3, d=9, b=6

substitute b and c to get f: (fifth equation)

at b=0, c=1, f=1 and at b=6, c=1, f=7

equations left after substitution of known values are: a=a , j=j, i/h=a

*here, you can substitute any value for a and j, since there are no more equations for us to solve their exact values,, since i and h depend on the value of a, we cannot determine their values,,

so there,, i hope i was able to help.. =)